Nucleotide Sequence Variation in MHC Class I Region in Guinea Fowl - Singh, S.K.; Mehra, S.; Shukla, S.K.; Kumar, Vinay; Tiwari, A.; Mehra, M.; Goyal, Giriraj; Mathew, Jose; Sharma, Deepak (International Journal of Poultry Science, 2010)
The MHC class I gene was amplified, cloned and sequenced in guinea fowl using the primers specific to BF2 gene in chicken. The nucleotide sequence of 571 bp partial CDS of BF2 gene includes 32 nucleotides of signal peptide (exon 1), complete α1 domain (270 nucleotides) and 269 nucleotides of α2 domain. For α1 and α domain no sequence variation was observed within guinea fowl sequences, however, high variability was observed within the other poultry species (15.93-28.03%) except chicken (7.95-9.16%). Between the guinea fowl and other poultry species, the α1 domain showed high nucleotide variability (29.26-43.70%). Among poultry species, guinea fowl showed least variability with chicken and maximum with duck. Among the substitutions, majorities were of non-synonymous (76.27%) with a ration of 1:3 between synonymous to non-synonymous substitutions. Guinea fowl showed lower genetic distances (Kimura 2-parameter) with chicken and quail (0.211-0.215), while with duck and goose, it showed higher genetic distances (0.343-0.350). Phylogenetic tree, based these genetic distances revealed two major clusters, comprising of guinea fowl, quail and chicken in one with guinea fowl as separate branch, while duck and goose in other.